First-Principles Calculations On Solgel Zinc Oxide Nanoparticles Optoelectronic Properties - Harun, Kausar (2018)
An efficient diagnostic between experimental and theoretical calculation is essential to ensure the synergy between these two approaches. This study made attempt to use structural input from experimental in the theoretical framework. Initially, ZnO nanoparticles were synthesized by sol-gel method at different aging time. The phase and structural analyses confirmed the formation of hexagonal wurtzite ZnO structure at which sample aged at 36 h showed highest crystallinity and gave the best visual fit in Rietveld analysis. Morphological observation revealed spherical nanoparticles were formed at aging time higher than 6 h while only small variation in energy band gap recorded between 3.08 – 3.12 eV. The photoluminescence spectra revealed a green emission due to oxygen vacany. In firstprinciples calculation, the ZnO unit cell was built based on structural parameter from Rietveld analysis in order to provide a bridge with experimental study. Several exchange-correlation functional including LDA, GGA-PBE, GGA-PBESol, LDA+U, GGA-PBE+U and GGA-PBESol+U were tested. The GGA-PBE+U (Ud,Zn = 10 eV and Up,O = 6.1 eV) showed lowest lattice deviation and successfully reproduced the experimental band gap. ZnO supercell structure with oxygen vacancy showed that defect state were more delocalized and appeared at 1.90 eV from top of conduction band. This position was close to the photon energy released due to recombination of electron (2.06 eV) as observed in luminescence spectra. The results are beneficial in designing photoanode material in solar cell that will enhance visible light absorption.